1998
DOI: 10.1172/jci445
|View full text |Cite
|
Sign up to set email alerts
|

Native low density lipoprotein-induced calcium transients trigger VCAM-1 and E-selectin expression in cultured human vascular endothelial cells.

Abstract: Low density lipoprotein (LDL) interactions with the endothelium are thought to play a major role in the development of atherosclerosis. The mechanism(s) involved are not fully understood, although several lines of evidence support the idea that oxidation of LDL increases its atherogenicity. In this study we report for the first time that native LDL (n-LDL) binding to the LDL receptor (100-700 mug/ml) triggers a rise in intracellular calcium which acts as a second messenger to induce vascular cell adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 57 publications
4
60
2
Order By: Relevance
“…In smooth muscle cells and endothelial cells, LDL induced the phosphoinositidedependent signaling pathway leading to an increase in cytosolic-free calcium through pertussis toxin-sensitive GTP-binding protein (47)(48)(49). In our study, monocytes responded similarly, and LDL induced a rapid and transient increase of the [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…In smooth muscle cells and endothelial cells, LDL induced the phosphoinositidedependent signaling pathway leading to an increase in cytosolic-free calcium through pertussis toxin-sensitive GTP-binding protein (47)(48)(49). In our study, monocytes responded similarly, and LDL induced a rapid and transient increase of the [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, HCAEC were preincubated with BAPTA/AM (10 M) for 30 min before the addition of nucleotides. U937 cells were labeled with the green fluorescent dye PKH2, as described previously (20). Labeled U937 cells (10 6 cells/well) were added to confluent cultures of HCAEC for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that native LDL induces vasoconstriction, 10 impairment of endothelium-dependent relaxation, 11,12 changes in intracellular calcium flux, 13 and VSMC proliferation. 14,15 Since the effects evoked by native LDL can be blocked by compounds inhibiting different intracellular pathways, even in the absence of the classical LDL receptor, 16 it is possible that LDL signals via a rather nonspecific second messenger, such as modulation of the cellular redox balance.…”
mentioning
confidence: 97%